Dietary Supplementation with Rutin Alters Meat Quality, Fatty Acid Profile, Antioxidant Capacity, and Expression Levels of Genes Associated with Lipid Metabolism in Breast Muscle of Qingyuan Partridge Chickens - Yuanfei Li; Huadi Mei; Yanchen Liu; Zhenming Li; Hammad Qamar; Miao Yu; Xianyong Ma (Foods, 2023)
Consumer demand for tasty and quality meat has been quickly increasing. This study investigated how dietary supplemented rutin affects meat quality, muscle fatty acid profile, and antioxidant capacity in the Chinese indigenous Qingyuan partridge chicken. A cohort of 180 healthy 119-day-old chickens was subjected to a randomized assignment into three groups, identified as the control, R200, and R400 groups, with respective supplementation of 0, 200, and 400 mg/kg of rutin. The results revealed insignificance in growth performance, namely, average daily gain, average daily feed intake, and feed-to-gain ratio, across the various treatment groups (p > 0.05). Nevertheless, dietary rutin supplementation increased (p < 0.05) breast muscle yield and intramuscular fat content in breast muscle and decreased (p < 0.05) drip loss in breast muscle. Rutin supplementation increased (p < 0.05) the content of high-density lipoprotein but decreased (p < 0.05) the contents of glucose, triglyceride, and total cholesterol in serum. Rutin supplementation increased (p < 0.05) the levels of DHA (C22:6n-3), total polyunsaturated fatty acids (PUFAs), n-3 PUFAs, decanoic acid (C10:0), the activity of Δ5 + Δ6 (22:6 (n − 3)/18:3 (n − 3)), and the ratio of PUFA/SFA in breast muscle but decreased (p < 0.05) the level of palmitoleic acid (C16:1n-7), the ratio of n-6/n-3 PUFAs, and the activity of Δ9 (16:1 (n − 7)/16:0). Rutin treatment also reduced (p < 0.05) the contents of malondialdehyde in serum and breast muscle, and increased (p < 0.05) the catalase activity and total antioxidant capacity in serum and breast muscle and the activity of total superoxide dismutase in serum. Additionally, rutin supplementation downregulated the expression of AMPKα and upregulated the expression of PPARG, FADS1, FAS, ELOVL7, NRF2, and CAT in breast muscle (p < 0.05). Convincingly, the results revealed that rutin supplementation improved meat quality, fatty acid profiles, especially n-3 PUFAs, and the antioxidant capacity of Qingyuan partridge chickens.